2017
DOI: 10.1007/s12038-017-9710-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple oncogenic roles of nuclear β-catenin

Abstract: β-Catenin is essential for embryonic development and required for cell renewal/regeneration in adult life. Cellular β-catenin exists in three different pools: membranous, cytoplasmic and nuclear. In this review, we focus on functions of the nuclear pool in relation to tumorigenesis. In the nucleus, beta-catenin functions as both activator and repressor of transcription in a context-dependent manner. It promotes cell proliferation and supports tumour growth by enhancing angiogenesis. β-Catenin-mediated signalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 185 publications
0
18
0
Order By: Relevance
“…Cellular β-catenin exists in three different pools: membranous, cytoplasmic, and nuclear [19]. Freshly synthesized β-catenin interacts with E-cadherin and serves as a structural protein localized to the cell membrane (membranous pool).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular β-catenin exists in three different pools: membranous, cytoplasmic, and nuclear [19]. Freshly synthesized β-catenin interacts with E-cadherin and serves as a structural protein localized to the cell membrane (membranous pool).…”
Section: Main Textmentioning
confidence: 99%
“…In contrast, destruction complex captures free β-catenin in the cytoplasm and rapidly targets it for degradation (cytoplasmic pool). Due to the compromised function of the destruction complex, β-catenin escapes degradation and translocates into the nucleus (nuclear pool) [19]. In different cell pools, β-catenin undergoes distinct regulation patterns and have diverse functions.…”
Section: Main Textmentioning
confidence: 99%
“…β-Catenin-mediated signaling regulates tumor initiation and progression in multiple malignancies [26]. Here, we analyzed the transcriptome data of esophageal cancer via the UALCAN data portal and found that the majority of genes in the pathway were differentially expressed in tumor tissues compared to normal tissues (Fig.…”
Section: Apatinib Regulated β-Catenin Signaling In Esophageal Cancermentioning
confidence: 99%
“…Nuclear positivity of β-catenin as a result of activated Wnt pathway has been previously detected in many other tumors (27). However, more recent studies show, that the translocation of β-catenin to nucleus is more likely a multi-factorial process than just a result of cytosolic accumulation of this molecule, even if the Wnt pathway is activated (28).…”
Section: Discussionmentioning
confidence: 94%